Modulation of gut microbiota through nutritional interventions in Behçet’s syndrome patients (the MAMBA study): study protocol for a randomized controlled trial - Pagliai, Giuditta; Dinu, Monica; Fiorillo, Claudia; Becatti, Matteo; Turroni, Silvia; Emmi, Giacomo; Sofi, Francesco (Current controlled trials in cardiovascular medicine, 2020)
Background Behçet’s syndrome (BS) is a systemic inflammatory disorder of unknown etiology, and it is characterized by a wide range of potential clinical manifestations. Recent evidence suggests that the gut microbiota (GM) in BS has low biodiversity with a significant depletion in butyrate producers. The aim of the present project is to investigate whether a dietary intervention could ameliorate the clinical manifestations and modulate the GM of individuals with BS. Methods This is a randomized, open, cross-over study that involves 90 individuals with BS, who will be randomly assigned to one of three different diets for 3 months: a lacto-ovo-vegetarian diet (VD), a Mediterranean diet (MD), or a Mediterranean diet supplemented with butyrate (MD-Bt). The VD will contain inulin-resistant and resistant-starch-rich foods, eggs, and dairy in addition to plant-based food, but it will not contain meat, poultry, or fish. The MD will contain all food categories and will provide two portions per week of fish and three portions per week of fresh and processed meat. The MD-Bt will be similar to the MD but supplemented with 1.8 g/day of oral butyrate. The three different diets will be isocaloric and related to the participants’ nutritional requirements. Anthropometric measurements, body composition, blood, and fecal samples will be obtained from each participant at the beginning and the end of each intervention phase. The primary outcomes will be represented by the change from baseline of the BS gastrointestinal and systemic symptoms. Changes from baseline in GM composition, short-chain fatty acid (SCFA) production, and the inflammatory and antioxidant profile will be considered as secondary outcomes. Discussion BS is a rare disease, and, actually, not all the available treatments are target therapies. A supportive treatment based on dietary and lifestyle issues, able to restore immune system homeostasis, could have a high impact on cost sustainability for the treatment of such a chronic and disabling inflammatory condition. Trial registration clinicaltrials.gov: NCT03962335 . Registered on 21 May 2019.